An inwardly rectifying whole cell current induced by G(q)-coupled receptors - Buchholz, Björn; Tauber, Robert; Steffl, Daniel; Walz, Gerd; Koettgen, Michael (Biochemical and Biophysical Research Communications, 2004)
Ca2+ influx across the plasma membrane after stimulation of G protein-coupled receptors is important for many physiological functions. Here we studied the regulation of an inwardly rectifying whole cell current and its putative role in Ca2+ entry in Xenopus oocytes. Expression of P2Y(1) or M1 receptors in Xenopus oocytes elicited a characteristic inwardly rectifying current without receptor stimulation. This current displayed distinct activation and inactivation kinetics and was highly Ca2+-dependent. After stimulation of endogenous G(q)-coupled receptors in water-injected cells similar currents were observed. We therefore speculated that the current could be activated via Ca2+ store depletion induced by constitutive stimulation of the IP3 cascade in cells overexpressing G(q)-coupled receptors. Receptor-independent Ca2+ store depletion also induced the current. In conclusion, this current is activated after store depletion suggesting a role in Ca2+ entry after stimulation of G(q)-coupled receptors. Finally, our data do not support the proposed ionotropic properties of the P2Y(1) receptor. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: G protein-coupled receptor; P2Y receptor; M1 receptor; Xenopus oocyte; store depletion; Ca2+ signaling; IP3; cascade; capacitative Ca2+ entry